IL11 activates the placental inflammasome to drive preeclampsia - Menkhorst, Ellen; Santos, Leilani L.; Zhou, Wei; Yang, Guannan; Winship, Amy L.; Rainczuk, Katarzyna E.; Nguyen, Philana; Zhang, Jian-Guo; Moore, Paddy; Williams, Michelle; Lê Cao, Kim-Anh; Mansell, Ashley; et al. (Frontiers in Immunology, 2023)
Preeclampsia is a life-threatening disorder of pregnancy unique to humans. Interleukin (IL)11 is elevated in serum from pregnancies that subsequently develop early-onset preeclampsia and pharmacological elevation of IL11 in pregnant mice causes the development of early-onset preeclampsia-like features (hypertension, proteinuria and fetal growth restriction). However, the mechanism by which IL11 drives preeclampsia is unknown. Pregnant mice were administered PEGylated (PEG)IL11 or control (PEG) from embryonic day (E)10-16 and the effect on inflammasome activation, systolic blood pressure (during gestation and at 50/90 days post-natal), placental development and fetal/post-natal pup growth measured. RNAseq analysis was performed on E13 placenta. Human 1st trimester placental villus were treated with IL11 and the effect on inflammasome activation and pyroptosis identified by immunohistochemistry and ELISA. PEGIL11 activated the placental inflammasome causing inflammation, fibrosis and acute and chronic hypertension in wild-type mice. Global and placental-specific loss of the inflammasome adaptor protein Asc and global loss of the Nlrp3 sensor protein prevented PEGIL11-induced fibrosis and hypertension in mice but did not prevent PEGIL11-induced fetal growth restriction or stillbirths. RNA-sequencing and histology identified that PEGIL11 inhibited trophoblast differentiation towards spongiotrophoblast and syncytiotrophoblast linages in mice and extravillous trophoblast linages in human placental villus. Inhibition of ASC/NLRP3 inflammasome activity could prevent IL11-induced inflammation and fibrosis in various disease states including preeclampsia.